Geoestratégia contemporânea: matriz energética na defesa e a importância da integração regional nos projetos energéticos - Vinícius Provensani (2019)
The “energy” agenda is linked in all aspects of contemporary life. Nothing involving current human existence exists or is unrelated to energy issues. To the same extent, the security and defense agenda linked to the domain of natural energy resources has been increasing. It is about Energy Security, in which natural resources are protagonists not only in the realization of the idea of Security, but also in the strengthening of State Sovereignty and foreign policy. This is evidenced by the direct and indirect performance of various states on the international stage, as regards the control of the most diverse energy matrices in the world. In this scenario, regional strengthening, through instruments and institutions, such as the IIRSA - South American Regional Integration Initiative, is important for the development of states, both in the economic sphere, as well as in security and defense. The purpose of this paper is to highlight regional integration, specifically the IIRSA, as well as a reflection framework that shows the need to ensure national security, stressing the importance of energy production and their sources, exemplified through regional energy integration planning through projects linked to that program.